Eksplorasi etnomatematika pada motif batik sicuriang ludai sebagai sumber belajar matematika - Nurrahmawati; Afri, Lusi Eka; Syafitri, Yuni (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Purpose: This study examines ethnomathematics within the Sicuriang Ludai batik motif to integrate local wisdom into the formal mathematics curriculum, effectively bridging the chasm between abstract theory and cultural reality. Design/methodology/approach: Utilizing an ethnographic design, data were gathered through participant observation and in-depth interviews with Rokan Hulu cultural experts. The data were then systematically analyzed through data condensation and verification techniques to ensure analytical rigor. Findings: The findings confirm the manifestation of plane geometry concepts—specifically rectangles and parallelograms—alongside angular relationships and geometric transformations, including translation, reflection, and rotation. Philosophically, these patterns represent the identity of the Rokan Hulu community through ingrained principles of mathematical precision. Practical implications: This research supports the implementation of culturally responsive pedagogy, providing a framework for educators to develop instructional materials that are both contextual and meaningful for students. Originality/value: As the inaugural scholarly documentation of the Sicuriang Ludai motif within a mathematical framework, this study underscores mathematics as a culture-bound entity and enriches the literature on indigenous-based learning resources in the Southeast Asian context. Purpose: Penelitian ini menganalisis etnomatematika pada motif batik Sicuriang Ludai untuk mengintegrasikan kearifan lokal ke dalam kurikulum matematika formal, sekaligus menjembatani celah antara teori abstrak dan realitas budaya. Design/methodology/approach: Melalui desain etnografi, data dikumpulkan melalui observasi partisipatif dan wawancara mendalam dengan budayawan Rokan Hulu, kemudian dianalisis secara sistematis menggunakan teknik kondensasi data dan verifikasi kesimpulan. Findings: Temuan mengonfirmasi manifestasi konsep geometri bidang (persegi panjang dan jajargenjang), hubungan sudut, serta transformasi geometri (translasi, refleksi, dan rotasi) pada motif batik. Secara filosofis, pola ini merepresentasikan identitas masyarakat melalui prinsip ketelitian matematis yang mendalam. Practical implications: Hasil penelitian ini mendukung implementasi pedagogi responsif budaya (culturally responsive pedagogy), memberikan kerangka bagi pendidik untuk menciptakan materi pembelajaran yang lebih kontekstual dan bermakna bagi siswa. Originality/value: Sebagai dokumentasi ilmiah pertama terhadap motif Sicuriang Ludai dalam konteks matematika, penelitian ini memperkuat posisi matematika sebagai entitas yang terikat budaya (culture-bound) dan memperkaya literatur sumber belajar berbasis kearifan lokal.